In situ oxidation of canola meal sinapic acid by horseradish peroxidase (type II) and tyrosinase. Issue 6 (6th May 2019) - Cao, Xinyuan; Liang, Jingbang; Aluko, Rotimi E.; Thiyam‐Holländer, Usha
Abstract: The enzymatic oxidation of sinapic acid catalyzed by horseradish peroxidase (HRP) or tyrosinase was investigated using model systems, which contained the pure compound or canola meal. Spectrophotometric scanning of pure sinapic acid solution in the presence of HRP (0.2 U) or tyrosinase (40.3 U) showed continuous decreases in absorbance at 304 nm over a period of 90 and 60 min, respectively. HPLC analyses of enzymatic end products, obtained by the catalysis with HRP or tyrosinase, indicated the presence of two main compounds (1 and 2). After alkaline hydrolysis of canola meal, sinapic acid that was released from sinapine was also converted to compounds 1 and 2 by HRP or tyrosinase. Enzyme reaction kinetics results indicate that the catalytic efficiency (CE = 0.538), reaction velocity (Vmax  = 5.67 ∆A/h), and Michaelis‐Menten constant (Km  = 926.64 µM) of HRP are significantly higher than those of tyrosinase (CE = 0.041, Vmax  = 0.41 ∆A/h, Km  = 173.03 µM) at 50–250 μM pure sinapic acid concentrations. Practical applications: Canola meal contains a large amount of sinapine, which is the choline ester of sinapic acid, a strong antioxidant compound. However, the oxidation or decarboxylation products of sinapic acid could add value by increasing the level of electron‐dense carboxylic and carbonyl compounds. In this study, enzymatic treatment of alkaline‐hydrolyzed canola meal with horseradish peroxidase (HRP) and tyrosinase was investigated and shown to be suitable for converting sinapic acid into oxidized compounds. Therefore, the enzymatic treatment is a potential application for value‐added processing of canola meal.